2014
DOI: 10.1021/am501448t
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Scaffolds Integrated with Calcium Sulfate and Oyster Shell for Enhanced Bone Tissue Regeneration

Abstract: Engineering scaffolds combinging natural biomineral and artificially synthesized material hold promising potential for bone tissue regeneration. In this study, novel bioactive calcium sulfate/oyster shell (CS/OS) composites were prepared. Comparing to CS scaffold, the CS/OS composites with a controllable degradation rate displayed enhanced mineral nodule formation, higher alkaline phosphate (ALP) activity and increased proliferation rate while treated osteocytes. In CS/OS composites group, elevated mRNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…COL1A1 encodes the major components of type‐I collagen . While OSX and OCN are late‐stage makers of calcium deposition and osteogenic differentiation . In terms of Sox9 , it is an essential transcription factor in the regulation of chondrocyte differentiation .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…COL1A1 encodes the major components of type‐I collagen . While OSX and OCN are late‐stage makers of calcium deposition and osteogenic differentiation . In terms of Sox9 , it is an essential transcription factor in the regulation of chondrocyte differentiation .…”
Section: Discussionsupporting
confidence: 92%
“…30 While OSX and OCN are late-stage makers of calcium deposition and osteogenic differentiation. 31 In terms of Sox9, it is an essential transcription factor in the regulation of chondrocyte differentiation. 32 In agreement with our findings, Wang SN et al showed that miR-193a could reduce the expression of osteoblast-specific markers (including Runx2, ALP, OSX, and OCN) by targetedly downregulating HMGB1 to inhibit the differentiation of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…HAp derived from cockle shells [74,75], oyster shells [76,77], mollusc shell [78] and eggshells [79] have been combined with different biomaterials to develop porous composite bone scaffolds.…”
Section: Shellsmentioning
confidence: 99%
“…Raman spectroscopy allowed for confirmation of aragonite crystals present in the matrix 14 . Bone regeneration initiated by nacre was proven in experiments in ovine bone defects, rabbit defects and human maxillofacial defects, illustrating the powerful role of nacre in bone regeneration 1619. …”
Section: Introductionmentioning
confidence: 98%